Utilization Of Stroke Early Detection Card : Stroke Risk Score Card In Detecting The Risk Of Stroke In The Environment Citizens Of Poltekkes Jakarta I - Tarwoto Tarwoto; Sri Handayani; Uun Nurulhuda; Fenti Hasnani; Zeni Zaenal Mutaqin (International Journal of Social Service and Research, 2022)
Community service activities carried out within the residents of the Ministry of Health Polytechnic of Jakarta have a positive impact in detecting the risk of stroke for residents. Using a stroke early detection card, namely the Risk Stroke Scorecard, participants can be identified with mild stroke risk, a warning risk, and a high risk of stroke. Based on the results of examinations, measurements, and interviews of 150 participants, it is known that the condition of body weight is almost balanced between ideal body weight (49.3%) with overweight and obese (49.7%), most of them are non-smokers (72, 7 %), most have no family history of stroke (83.3 %), most of the blood pressure is abnormal ( 58 %), most of the heart rate is regular (96.7 %), the state of blood sugar when mostly average (58.7%), most of the cholesterol condition is not normal (60%). The analysis using the Stroke Risk Card showed that most of the participants had a warning stroke risk (48.7%).